In vivo synaptic density relates to glucose metabolism at rest in healthy subjects, but is strongly modulated by regional differences - van Aalst, June; Ceccarini, Jenny; Sunaert, Stefan; Dupont, Patrick; Koole, Michel; Van Laere, Koen (Journal of cerebral blood flow and metabolism, 2021)
Preclinical and postmortem studies have suggested that regional synaptic density and glucose consumption (CMRGlc) are strongly related. However, the relation between synaptic density and cerebral glucose metabolism in the human brain has not directly been assessed in vivo. Using [11C]UCB-J binding to synaptic vesicle glycoprotein 2 A (SV2A) as indicator for synaptic density and [18F]FDG for measuring cerebral glucose consumption, we studied twenty healthy female subjects (age 29.6 ± 9.9 yrs) who underwent a single-day dual-tracer protocol (GE Signa PET-MR). Global measures of absolute and relative CMRGlc and specific binding of [11C]UCB-J were indeed highly significantly correlated (r > 0.47, p < 0.001). However, regional differences in relative [18F]FDG and [11C]UCB-J uptake were observed, with up to 19% higher [11C]UCB-J uptake in the medial temporal lobe (MTL) and up to 17% higher glucose metabolism in frontal and motor-related areas and thalamus. This pattern has a considerable overlap with the brain regions showing different levels of aerobic glycolysis. Regionally varying energy demands of inhibitory and excitatory synapses at rest may also contribute to this difference. Being unaffected by astroglial and/or microglial energy demands, changes in synaptic density in the MTL may therefore be more sensitive to early detection of pathological conditions compared to changes in glucose metabolism.